2008
DOI: 10.1007/s10528-008-9161-y
|View full text |Cite
|
Sign up to set email alerts
|

No Correlation Between Heterozygosity and Vegetative Fitness in the Narrow Endemic and Critically Endangered Clematis acerifolia (Ranunculaceae)

Abstract: The relationship between heretozygosity and vegetative fitness was explored in the narrow endemic and threatened Clematis acerifolia (Ranunculaceae), both at individual and population levels. The relationships between fitness, habitat factors, and population size were also analyzed. Allozyme electrophoresis was used to quantify the levels of heterozygosity of nearly 200 surveyed individuals belonging to the nine extant populations of this species. Six parameters of vegetative fitness were measured: plant heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Various categories of genetic markers are used for this purpose: allozymes (Krzakowa & Michalak, 2007; López-Pujol, Zhang & Ge, 2008; Trapnell, Hamrick & Negrón-Ortiz, 2012; Dostálek, Münzbergová & Plačková, 2014), amplified fragment length polymorphism (AFLP) markers (Jian et al, 2010; Cires, Cuesta & Fernández Prieto, 2013; Wróblewska, 2013), random amplified polymorphic DNA (RAPD) markers (Wróblewska et al, 2003; Hensen, Oberprieler & Wesche, 2005; Hensen et al, 2010), restriction fragment length polymorphism (RFLP) markers (Schlögl, Souza & Nodari, 2007; Jadwiszczak et al, 2012; Jian & Zhu, 2013), inter simple sequence repeats (ISSR) markers (Buczkowska et al, 2010; Cires, Cuesta & Fernández Prieto, 2013; Gaafar, Al-Qurainy & Khan, 2014; Lopes et al, 2014) and single nucleotide polymorphism (SNP) markers (Bradley et al, 2013; Cipollini et al, 2013; Olsson & Korpelainen, 2013). These markers enable estimation of important genetic variation parameters (allelic richness, heterozygosity H , fixation index F is , pairwise F ST ).…”
Section: Introductionmentioning
confidence: 99%
“…Various categories of genetic markers are used for this purpose: allozymes (Krzakowa & Michalak, 2007; López-Pujol, Zhang & Ge, 2008; Trapnell, Hamrick & Negrón-Ortiz, 2012; Dostálek, Münzbergová & Plačková, 2014), amplified fragment length polymorphism (AFLP) markers (Jian et al, 2010; Cires, Cuesta & Fernández Prieto, 2013; Wróblewska, 2013), random amplified polymorphic DNA (RAPD) markers (Wróblewska et al, 2003; Hensen, Oberprieler & Wesche, 2005; Hensen et al, 2010), restriction fragment length polymorphism (RFLP) markers (Schlögl, Souza & Nodari, 2007; Jadwiszczak et al, 2012; Jian & Zhu, 2013), inter simple sequence repeats (ISSR) markers (Buczkowska et al, 2010; Cires, Cuesta & Fernández Prieto, 2013; Gaafar, Al-Qurainy & Khan, 2014; Lopes et al, 2014) and single nucleotide polymorphism (SNP) markers (Bradley et al, 2013; Cipollini et al, 2013; Olsson & Korpelainen, 2013). These markers enable estimation of important genetic variation parameters (allelic richness, heterozygosity H , fixation index F is , pairwise F ST ).…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between individual genomic-wide general heterozygosity and phenotypic traits have been studied both in both animals and plants [ 8 , 9 , 24 , 29 , 50 ]. According to previous studies, the relationships between individual genome-wide general heterozygosity and traits were very sophisticated and might differ with respect to sampling species and assessment procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although a general trend of a significant positive correlation was reported between genetic diversity and population fitness in meta‐analysis studies (Reed and Frankham, 2003; Leimu et al, 2006), no correlation was observed between genetic diversity and population fitness in Clematis acerifolia Maxim. (Lopez‐Pujol et al, 2008). For the Searls prairie clover collections, correlation coefficients between PC scores obtained from phenotypic measurements and the within‐collection genetic similarity (the opposite of genetic diversity) obtained from AFLP analysis were not significant.…”
Section: Discussionmentioning
confidence: 99%